Development of a DC-AC power conditioner for wind generator by using fuzzy logic - Mohamed Jelwal, Faisel (2011)
In this project, a fuzzy logic controller is designed to obtain the desired output voltage of DC-AC power conditioner used in a stand alone wind generator which the Fuzzy Logic Controller (FLC) is employed to control the modulation index of the SPWM (Sinusoidal -Pulse Width-Modulation) inverter which is built using four MOSFET’s transistor. This project present of development single phase DC-AC converter for wind generator application. The mathematical model of the wind generator and Fuzzy Logic Controller for DC-AC converter is derived. The controller is designed to stabilize the output voltage of DC-AC converter. To verify the effectiveness of the proposal controller, both simulation and experimental are developed. The simulation and experimental result show that the amplitude of output voltage of the DC-AC converter can be controlled.